Exploration of Aberrant E3 Ligases Implicated in Alzheimer’s Disease and Development of Chemical Tools to Modulate Their Function - Potjewyd, Frances M.; Axtman, Alison D. (Frontiers in Cellular Neuroscience, 2021)
The Ubiquitin Proteasome System (UPS) is responsible for the degradation of misfolded or aggregated proteins via a multistep ATP-dependent proteolytic mechanism. This process involves a cascade of ubiquitin (Ub) transfer steps from E1 to E2 to E3 ligase. The E3 ligase transfers Ub to a targeted protein that is brought to the proteasome for degradation. The inability of the UPS to remove misfolded or aggregated proteins due to UPS dysfunction is commonly observed in neurodegenerative diseases, such as Alzheimer’s disease (AD). UPS dysfunction in AD drives disease pathology and is associated with the common hallmarks such as amyloid-β (Aβ) accumulation and tau hyperphosphorylation, among others. E3 ligases are key members of the UPS machinery and dysfunction or changes in their expression can propagate other aberrant processes that accelerate AD pathology. The upregulation or downregulation of expression or activity of E3 ligases responsible for these processes results in changes in protein levels of E3 ligase substrates, many of which represent key proteins that propagate AD. A powerful way to better characterize UPS dysfunction in AD and the role of individual E3 ligases is via the use of high-quality chemical tools that bind and modulate specific E3 ligases. Furthermore, through combining gene editing with recent advances in 3D cell culture, in vitro modeling of AD in a dish has become more relevant and possible. These cell-based models of AD allow for study of specific pathways and mechanisms as well as characterization of the role E3 ligases play in driving AD. In this review, we outline the key mechanisms of UPS dysregulation linked to E3 ligases in AD and highlight the currently available chemical modulators. We present several key approaches for E3 ligase ligand discovery being employed with respect to distinct classes of E3 ligases. Where possible, specific examples of the use of cultured neurons to delineate E3 ligase biology have been captured. Finally, utilizing the available ligands for E3 ligases in the design of proteolysis targeting chimeras (PROTACs) to degrade aberrant proteins is a novel strategy for AD, and we explore the prospects of PROTACs as AD therapeutics.